Soluble form of carbonic anhydrase IX (CAIX) in transitional cell carcinoma of urinary tract - Hyrsl, L; Zavada, J; Zavadova, Z; Kawaciuk, I; Vesely, S; Skapa, P (Neoplasma, 2009)
We investigated the expression of cell-associated CAIX protein in histological sections of the transitional cell carcinoma (TCC) of the urinary tract and of the soluble form of CAIX (s-CAIX) shed by the tumor into the serum and urine of TCC patients. A total of 23 patients with histologically confirmed TCC or squamous cell carcinoma (SCC) were enrolled in the pilot study. Sixteen healthy individuals served as controls. Membrane-bound CAIX was present in the tumor cells near the endoluminal surface. Necrosis was observed in only 4 samples. Using Western blots, s-CAIX concentrated from urine was visualized as a double band at 50 and 54 kDa. In most cases, the presence of s-CAIX in the urine correlated with CAIX expression in the tumor. On the other hand, s-CAIX did not exceed the normal level in the serum of TCC patients. Urine from patients with TCC of the urinary bladder and renal pelvis contained s-CAIX, allowing the detection of tumors in approximately 70% of the patients. Moreover, two additional patients with suspected, but unconfirmed bladder tumor, with s-CAIX detected in urine, developed tumors identified as TCC within six months. We suggest that after a simple, rapid and sensitive test, monitoring s-CAIX levels in urine will be developed, it may be useful for early detection of relapse in patients following transurethral tumor resection.
Keywords: buněčná membrána; Humans; Case-Control Studies; lidé středního věku; Carbonic Anhydrase IX; studie případů a kontrol; karcinom z přechodných buněk; Biomarkers, Tumor; Immunoenzyme Techniques; urologické nádory; Female; Aged; mladý dospělý; dospělí; Blotting, Western; močový měchýř; ELISA; Kidney Pelvis; senioři; karboanhydrasa IX; lidé; Antigens, Neoplasm; Enzyme-Linked Immunosorbent Assay; pilotní projekty; Pilot Projects; karboanhydrasy; antigeny nádorové; Urologic Neoplasms; ledvinná pánvička; nádorové biomarkery; Adult; imunoenzymatické techniky; staging nádorů; ženské pohlaví; Male; Middle Aged; prognóza; Carcinoma, Transitional Cell; Urinary Bladder; Aged, 80 and over; Young Adult; senioři nad 80 let; Neoplasm Staging; Cell Membrane; western blotting; mužské pohlaví; Carbonic Anhydrases; Prognosis